LOVE BIODIVERSITY EDUCATION TO CONFRONT AEC - Dimas Fahrudin; Susanti Susanti (Proceedings Education and Language International Conference, 2017)
Asean Economic Community (AEC) provide challenges and opportunities towards the progress of the nation. However, the AEC also had an impact on the degradation of character. Indonesia is a rich country local wisdom and biodiversity. Those elements is the principal element which interrelated to each other. As well as thats happends in the Gondang village slopes of Mount Ungaran, Central Java where the community maintain biodiversity through local wisdom. However, nowadays many happends character degradation of society on the slopes of Mount Ungaran, Gondang villages, so that impact on the degradation of biodiversity on Mount Ungaran. It is due to the large number of young people who leave the values of local wisdom and concern about the Biodiversity is diminshing. This is a threat to the sustainability of local wisdom and biodiversity at Mount Ungaran, remembers the importance of both these elements in the preservation of ecosystems, as well as the strengthening the character of nation identity through local wisdom. To maintain continuity, the characteristics of local wisdom and biodiversity on the slopes of Mount ungaran in confront of AEC, so required the existence of a significant stepin addressing the problem. One of the is through educational programs for love biodiversity which is an educational program that aims to educate children around the forest or region with the highest biodiversity with the aim to foster the cultural characters of local wisdom as well as improving the character of biodiversity (preserving biodiversity character). The concept of the program is education by utilizing the natural environtment. Students are invited to explore the natural environtment and local wisdom. The purpose of the program is the presence generations love biodiversity-based on local wisdom. Then biodiversity will remain awake and local wisdom will be a character in each student's and identity of nation in confront AEC.Keywords: biodiversity, local wisdom. The character of biodiversity. Love Biodiversity Educational Programs.